RARRES3 suppressed metastasis through suppression of MTDH to regulate epithelial-mesenchymal transition in colorectal cancer - Wang, Zhengting (Am J Cancer Res, 2015)
It has been reported that Retinoic acid receptor responder 3 (RARRES3) could suppress the metastasis of colorectal cancer (CRC). However, the underlying mechanism by which RARRES3 suppresses metastasis remains unknown. To investigate the functional involvement of RARRES3 in CRC, we first analyzed the expression of this protein between human CRC clinical samples and their corresponding normal controls and tested its correlation with clinicopathology as well as prognosis of CRC. We also examined the endogenous expression of RARRES3 by western-blot in a panel of CRC cell lines with different metastatic capacity. Cell proliferation, migration and invation of the CRC cell lines with either knockdown or reexpression of RARRES3 were examined by MTT, transwell and wound healing assays, respectively. The intrecellular signaling pathways affected by manipulations of RARRES3 in CRC cells were determined by western blot. Immunoprecipitation (IP) was employed to assess the interactionbetween proteins. To investigate the metastatic ability in vivo, CRC cell lines with manipulations of RARRES3 expression were inoculated in nude mice through tail vein injection. We confirmed that RARRES3 was significantly down-regulated in CRC tissues compared with normal controls. RARRES3 expression was not correlated with prognosis but significantly associated with CRC differentiation and lymphnodes metastases. We also found that RARRES3 was able to significantly suppress the metastasis of CRC cells both in vitro and in vivo through the regulation of epithelial-mesenchymal transition (EMT) process during which RARRES3 interactedwith MTDH in an opposite way. Taken together, we for the first time found that RARRES3 was able to suppress the metastasis of CRC both in vitro and in vivo via suppression of MTDH so as to regulate EMT.